(untitled) (Research, Society and Development, 2023)
Introduction: Gestational low back pain (GLBP) have impact on performance of daily life activities, although it remains uncertain the impact of pain intensity in clinical outcomes. Aims: To verify the impact and relationship of pain intensity of GLBP on quality of life (QoL), sleep quality (SQ), functional status, anxiety and depression. Methods: Pregnant women above 20 weeks of gestation completed the sample characterization form and answered five questionnaires to assess pain (Visual Analogue Scale), QoL (Medical Outcomes Short Form Health Survey–36 item), SQ (Pittsburg Sleep Quality Index), functional status (Oswestry Disability Index), anxiety and depression (Hospital Anxiety and Depression Scale). Participants were divided in two groups, with GLBP (GLBP group) and without GLBP (CG). GLBP group was stratified according to pain intensity in two groups: mild pain (VAS≤3: M-GLBP) and moderate to severe pain (VAS>3: MS-GLBP). Results: 75 participants were included, 75% in the GLBP (n=56, 30[27-34] years) and 25% in CG (n=19, 32[30-34] years). GLBP presents worse QoL, SQ, functional status, anxiety and depression (p<0.05). MS-GLBP (n=32) had worse SQ (p=0.006), functional status (p<0.0001), anxiety and depression (p<0.05) compared to CG and present worse QoL (p<0.05) compared to M-GLBP (n=24). M-GLBP has worse functional status compared to CG (p<0.001). Pain intensity is moderately correlated to functional status (r=0.56; p<0.0001). Conclusion: Women with moderate to severe GLBP presented worse QoL, SQ, functional status, increased depression and anxiety compared to CG, even mild GLBP have impact on functional status and pain intensity have moderate correlation with functional status.